Microalgae and the medicine of the future - Pereira, Julianne Soares; Gomes, Keyla Nunes Farias; Pereira, Caroline de Souza Ferreira; Jardim, Geovana Espíndola; Santiago, Patrícia Soares; Rocha, Leandro Machado; Faria, Robson Xavier (Seven Editora, 2023)
This chapter looks at the biotechnological potential of microalgae and their promising use in medicine. We explore their applications as bioreactors in producing pharmaceutical substances and their innovative capacity in gene therapy. In addition, we highlight the growing interest in their nutritional properties, especially omega-3 fatty acids, and high-quality antioxidants. Our analysis also showed the impact of microalgae in the field of vaccines and immunotherapies, highlighting their ability to improve the efficacy of vaccines and drive the development of advanced immunization methods. We discussed current challenges and prospects in the broader context, highlighting the continued need for in-depth research and investment in this emerging area. This chapter has aimed to provide a comprehensive overview of the transformative potential of microalgae in medicine, emphasizing their role as one of the fundamental pillars for the continued advancement of human health and the development of innovative therapies on the horizon of future medicine. Hopefully, this analysis will stimulate further discussion and inspire new research, thus driving progress biomedical research. DOI:https://doi.org/10.56238/sevened2023.007-001